Representation of Indonesian Society in Covid-19 Pandemic on Illustration Work in Instagram Accounts @Harimerdeka and @Micecartoon: Semiotics Study - Yuni Syafria Br Hasibuan; Eddy Setia; T. Thyrhaya Zein (Budapest International Research and Critics University, 2022)
This study examines the signs, meanings and representations of Indonesian people during the Covid-19 pandemic in illustrations on Instagram social media accounts. This study uses a qualitative approach with a descriptive method. The analysis used in this study uses the semiotic theory of Charles Sanders Pierce's trichotomy (triadic). The data in this study are uploaded image illustrations sourced from the @harimerdeka and @micecartoon accounts. Data collection using documentation techniques. Analysis of the data in this study using the interactive analytical model of Miles, Huberman & Saldana. The results of the study found various signs in the representament and object elements in the form of colors, icons and symbols.